(untitled) - Muir, John (Washington, 2001)
John Muir's Last Journey provides a rare glimpse of a Muir whose interests as a naturalist, traveler, and conservationist extended well beyond the mountains of California. It also helps us to see Muir as a different kind of hero, one whose endurance and intellectual curiosity carried him into far fields of adventure even as he aged, and as a private person and family man with genuine affections, ambitions, and fears, not just an iconic representative of American wilderness.
Keywords: Lịch sử thiên nhiên,Travel,Natural history,Du lịch; Nam Mỹ,South America,South America,Nam Mỹ